What a wonderful world - Weiss, George (George David); Thiele, Bob.; Bryan, Ashley (New York, NY : Atheneum Books for Young Readers, 1995)
Children put on a puppet show using the words to the song "What a Wonderful World," made famous by Louis Armstrong.
"A Jean Karl book."
Keywords: Armstrong, Louis, -- 1901-1971 -- Juvenile fiction; Armstrong, Louis, -- 1901-1971 -- Fiction; Puppet theater -- Fiction; Stories in rhyme